Relationship between perioperative thyroid function and acute kidney injury after thyroidectomy - Joo, Eun-Young (Sci Rep, 2018)
Thyroid dysfunction may alter kidney function via direct renal effects and systemic haemodynamic effects, but information on the effect of thyroid function on postoperative acute kidney injury (AKI) following thyroidectomy remains scarce. We reviewed the medical records of 486 patients who underwent thyroidectomy between January 2010 and December 2014. Thyroid function was evaluated based on the free thyroxine or thyroid stimulating hormone levels. The presence of postoperative AKI was determined using the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. AKI developed in 24 (4.9%) patients after thyroidectomy. There was no association between preoperative thyroid function and postoperative AKI. Patients with postoperative hypothyroidism showed a higher incidence of AKI than patients with normal thyroid function or hyperthyroidism (19.4%, 6.7%, and 0%, respectively; P = 0.044). Multivariable logistic regression analysis showed that male sex (OR, 4.45; 95% CI, 1.80–11.82; P = 0.002), preoperative use of beta-blockers (OR, 4.81; 95% CI, 1.24–16.50; P = 0.016), low preoperative serum albumin levels (OR, 0.29; 95% CI, 0.11–0.76; P = 0.011), and colloid administration (OR, 5.18; 95% CI, 1.42–18.15; P = 0.011) were associated with postoperative AKI. Our results showed that postoperative hypothyroidism might increase the incidence of AKI after thyroidectomy.